Toxicity Test of Essential Oil from Kintamani Slayer Orange Peel (Citrus Reticulata) With Zero Waste Application to Support Ecotourism - Ni Luh Putu Putri Setianingsih; I Wayan Sudiarta; I Putu Candra; Ni Made Andira Padmarini; Gusti Ayu Yunda Darma Patni (International Journal of Scientific Multidisciplinary Research, 2024)
Kintamani slayer orange peel can be extracted into essential oil because it contains terpenoids, sesquiterpenoids, alkanes, alkyl alkanoates, and steroid alcohols. Orange peel contains active substances that can help heal wounds, such as essential oils, ascorbic acid, vitamin E, vitamin A, flavonoids, and polyphenols, and has antioxidant and antibacterial activity. Kintamani orange peel contains flavonoids, alkaloids, saponins, tannins, terpenoids, and essential oils. The main goal of this study is to identify the waste by-product characteristics of Kintamani slayer orange peel in order to achieve zero waste.  Essential oils in Kintamani slayer orange peel (Citrus reticulata) are toxic to Artemia salina Leach shrimp larvae. The GC results on Kintamani slayer orange peel essential oil obtained twelve (12) compound peaks